ANALISIS REALISASI BIAYA OPERASIONAL PENGUPASAN COAL GETTING KHUSUS ALAT UTAMA PENAMBANGAN DI PT DUTA ALAM SUMATERA SITE PT XYZ KABUPATEN LAHAT PROVINSI SUMATERA SELATAN - M. Ikbal Aziz; Lina Rianti; Tia Oktarina (Jurnal Cakrawala Ilmiah, 2023)
Mining activities will definitely require calculation in mining cost. Operational cost can effect the company’s revenue, so an analysis of operational costs is necessary. This study aimed to calculate the estimated production and actual production of coal getting in March 2023 and to calculate the operational costs of estimated production and actual production of coal getting in March 2023. The analysis process was carried out by determining the estimation and realization of coal getting production where the estimated production of coal getting was 35000 tons with 1 unit of digging equipment and 5 units of hauling equipment with operational costs for coal getting production incluiding the realization of diesel fuel of Rp76,926,810.00, oil of Rp500,000.00, operator salary of Rp5,400,000.00, repair/maintenance of Rp42,980,000.00, grease of Rp239,267.00, and Liugong Excavator filter of Rp300,000.00. those were lower than the estimated costs of diesel fuel of Rp103,647,600.00, oil of Rp4,000,000.00, operator salary of Rp10,800,000.00, repair/maintenance of Rp76,680,000.00, grease pf Rp3,800,000.00, and filters of Rp2,100,000.00. whereas for the Dongfeng Dump Truck, the actual costs of diesel was Rp25,000,000.00, oil cost was Rp360,000.00, operator salary cost was Rp25,000,000.00, spare parts cost was Rp270,000.00, grease cost was Rp656,355.00, filter cost was Rp300,000.00, and tires cost was Rp705,000.00 which were lower than the estimated cost of diesel fuel of Rp483,688,800.00, oil of Rp4,000,000.00, operator salary of Rp50,000,000.00, repair/maintenance of Rp76,680,000.00, grease of Rp3,800,000.00, filters of Rp2,100,000.00 and tires of Rp18,350,000.00. thus, the estmated operational cost was Rp777,589,300.00 and the realization was IDR 282,819,689.00.